THE URGENCY OF TEACHER'S ROLE IN IMPROVING THE COLERICAL PERSONALITY OF DEAF CHILDREN IN SLB PGRI PAMEKASAN - Apatikah, Nur Absar; Wahyudi, Heri Fadli (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The role of a teacher in educating, teaching, guiding and improving the personality of students is something that is absolutely essential. Because it is known that the role of teachers is very significant in forming a strong, independent and confident personality. Choleric personality is a personality that is full of ambition, self confident and likes to lead. Meanwhile deaf children are children who have hearing impairments, so they really need to develop a self confident personality. So to find out more deeply the researcher used data collection techniques namely structured interviews, non participant observation and documentation. So this research shows that the role of teachers at SLB PGRI Pamekasan in improving choleric, personality is as educators, mentors, motivators and facilitators and developers of students potential, where teachers have several strategies in building good communication with sign language, facial expressions and body movements and so on, making it easier for teachers improve the choleric personality of deaf children.